2005
DOI: 10.1007/s10541-005-0234-9
|View full text |Cite
|
Sign up to set email alerts
|

Location of the Bases Modified by M.BcoKIA and M.BcoKIB Methylases in the Sequence 5′-CTCTTC-3′/5′-GAAGAG-3′

Abstract: The strain Bacillus coagulans K contains two DNA-methyltransferases, M.BcoKIA and M.BcoKIB, which recognize the sequence 5 -CTCTTC-3 /5 -GAAGAG-3 and possess N4-methylcytosine and N6-methyladenine specificities, respectively. A special construct containing the recognition site of BcoKI and sites of four IIS restriction endonucleases (IIS restriction endonuclease cassette) was designed to locate the nucleotides modified by the methylases. The modified bases were determined as: 5 -m(4)CTCTTC-3 /5 -GAAGAm(6)G-3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Our SMRT sequencing analysis has indicated that M.TdeII carries out an m4C modification in one strand (5′- m4 CTCTTCNG-3′) and another m6A modification in the opposite strand (5′-G m6 AAGAG-3′). A single Type II R-M system in Bacillus coagulans has been shown to recognize the sequence 5′-CTCTTC-3′/5′-GAAGAG-3′ and converts the first cytosine to N4-methylcytosine in one strand and the second adenine to N6-methyladenine in the opposite strand ( 68 ). However, in that case, the two strands are separately methylated by two MTases (M1.BcoKI and M2.BcoKI) encoded by different hsdM genes.…”
Section: Discussionmentioning
confidence: 99%
“…Our SMRT sequencing analysis has indicated that M.TdeII carries out an m4C modification in one strand (5′- m4 CTCTTCNG-3′) and another m6A modification in the opposite strand (5′-G m6 AAGAG-3′). A single Type II R-M system in Bacillus coagulans has been shown to recognize the sequence 5′-CTCTTC-3′/5′-GAAGAG-3′ and converts the first cytosine to N4-methylcytosine in one strand and the second adenine to N6-methyladenine in the opposite strand ( 68 ). However, in that case, the two strands are separately methylated by two MTases (M1.BcoKI and M2.BcoKI) encoded by different hsdM genes.…”
Section: Discussionmentioning
confidence: 99%